‘The Social Managers Are Back in Town’: the Challenges of Housing Management in a Residualised Public Housing Sector - Igor Costarelli (Critical Housing Analysis)
The residualisation of social housing sectors requires housing managers to intensify social management activities aimed at promoting tenants’ wellbeing and social cohesion. This paper discusses the implementation of such activities in the Italian public housing sector. It juxtaposes the vision conceptualised at the policy level with the daily activities of housing managers in practice on the ground and highlights the gaps between policy goals and realities of tenants’ involvement. While social management activities are expected to contribute to breaking the vicious circle of financial, technical, and social decline that has long affected public housing estates, the short timeframe of the planned interventions raises the question of the potential for structural change.